The Effects of UV-LED Technology on the Quality of Ready-to-Eat Pomegranates: Epigenetic Indicators and Metabolomic Analysis - Aihemaitijiang Aihaiti; Yuanpeng Li; Xinmeng Huang; Yuting Yang; Ailikemu Mulati; Jiayi Wang (Foods)
Pomegranates are rich in nutrients and classified among ready-to-eat fruits and vegetables. Although this ready-to-eat produce offers convenience, it presents risks associated with pathogenic microorganisms, highlighting the need for pre-sale disinfection. Ultraviolet light-emitting diodes (UV-LEDs) constitute an innovative non-thermal processing technology for food products, offering reduced heat generation and lower energy consumption compared to traditional ultraviolet (UV) irradiation methods. This study analyzed the effects of UV-LED technology on pomegranate seed quality over 0 to 5 days of storage. The results demonstrated significant increases in anthocyanins, polyphenols, ascorbic acid, and the antioxidant capacity in pomegranate following treatment, peaking on day 3. In contrast, the control group showed declining trends. After treatment, the aerobic mesophilic counts and counts of mold and yeast levels during storage measured between 2.73–3.23 log CFU/g and 2.56–3.29 log CFU/g, respectively, significantly lower than the control group. Non-targeted metabolomic analysis showed that UV-LED treatment prompted modifications in the biosynthetic pathways of flavonoids, flavonols, and anthocyanins. The expression of peonidin-3-O-rutinoside chloride increased by 46.46-fold within the anthocyanin biosynthesis pathway. In conclusion, UV-LED treatment represents a potential approach to the disinfection of ready-to-eat fruits and vegetables.